Oncocytic Carcinoma of the Cranio-Orbital Area: A Case Report - Yang, Peng; Jiang, Libin; Liu, Honggang; Zhang, Jialiang; Kang, Jun (Frontiers in Surgery, 2022)
Background: Oncocytic carcinoma is a proliferation of malignant eosinophils with the structural characteristics of adenocarcinoma, an invasive eosinophilic carcinoma of the salivary gland. Methods:This article reports the first case of oncocytic carcinoma involving the cranio-orbital area. The oncocytic carcinoma in a patient with a sudden decrease in right eye vision is removed through a frontal orbital approach craniotomy. This course demonstrates rapid development. The patient is admitted to the neurosurgery department for a combined operation after ophthalmological screening. Results: Postoperative pathological analysis showed that the tumour cells were large, round or polygonal, and the cytoplasm was finely granular, which appeared to be more pleomorphic than eosinophilic adenoma. This report introduces the clinical process. Oncocytic carcinoma in the cranio-orbital area is extremely rare. Conclusion: Early resection to be done jointly by ophthalmology and neurosurgery is the most effective treatment, and long-term follow-up and adjuvant chemoradiotherapy are beneficial.